The discovery of potent agonists for GPR88, an orphan GPCR, for the potential treatment of CNS disorders. Issue 7 (1st April 2015) - Bi, Yingzhi; Dzierba, Carolyn D.; Fink, Cynthia; Garcia, Yudith; Green, Michael; Han, Jianxin; Kwon, Soojin; Kumi, Godwin; Liang, Zhi; Liu, Ying; Qiao, Ying; Zhang, Yulian; et al.
Graphical abstract: Abstract: Modulating GPR88 activity is suggested to have therapeutic utility in the treatment of CNS disorders, such as schizophrenia. This Letter will describe the discovery and SAR development of a class of potent GPR88 agonists.